A Review on the Influence of Nutritional Status on Cognition Performance of School Going Children - Khushnuma; Azeem, Jauhar; Naqeeb, Huma; Zeb, Zarafshan; Mehboob, Najma; Bilal; Bibi, Ayesha (Indus Journal of Bioscience Research, 2025)
Most of the children have poor nutritional status all over the world, which affect the children life in different ways. One of the impacts is nutritional status which influences the cognitive performance of school going children. The aim of this review was to determine the influence of nutritional status on the cognitive performance of school going children. Study was searched from the databases (google scholar, PubMed, sciHub). Studies with cognitive performance of school going children at the age between 5 and 14 were cited for the review. The aim of the review is to find how diet affects the cognitive performance of children and to identify how diet is associated with school performance. The review evaluated that diet high in nutrition, micro nutrients, intake of fructose, soluble fiber, total fiber, leafy vegetables, breakfast, breakfast high in macro nutrients composition, school feeding programs can positively associated with cognitive function. Poor nutrition status, nutrition deficiencies, malnutrition, stunting wasting are negatively associated with cognitive function. There is no significant association between dietary fats with cognitive function. Adequate intake of macronutrients (Carbohydrates, proteins, fats) and micronutrients (vitamins and minerals) can help in cognitive function. Majority of other factors are also included to esenhance the cognitive performance.